CHARACTERISTIC STRUCTUR MICRO HOT ROLLED PLATE STEEL VARIANS RADIUS BENDING WITH HEAT TREATMENT QUENCH-TEMPER - Taufik, Achmad (Journal of Applied Engineering Science, 2018)
Abstract : Hot Roll Plate Steel (HRPS) is a heat treatable steel made by PT Krakatau Steel Indonesia, HRP Steel specifications classified as steel armor. To get high hardness and strength, HRP Steel is heated by method quenching and temperature austenite is held for a while, then cooled with water media. Furthermore HRP Steel was reheated by tempering to temperature below the line eutectoid and held for a while and then cooled with atmospheric air to increase its plasticity (ductility). The purpose of obtaining heat treatment is to improve microstructure that can affect the value of violence. The method used in this study is divided into 2 treatments, namely bending treatment with a radius of 55mm and 60mm and treatment for heat treatment with quenching temperature of 800 ˚C holding 15 minutes and quenching tempering temperature of 150 ˚C holding 45 minutes. The results of the analysis showed that the bending treatment and heat treatment of the morphology of the microstructure changed. In the bending treatment radius of 55mm and quenching-tempering treatment has a higher percentage of martensitic microstructure and a smooth martensitic structure so that the vickers hardness value is higher than the 453 VHN treatment. Keywords : Bending, Heat Treatment, Struktur Mikro
Keywords: microstructures; heat treatments; bending